Evaluating Digital Readiness for Adopting Mobile-Based Public Service Information Systems in Rural Areas - Santoso, Lukman (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In recent years, the Indonesian government has actively promoted digital transformation in public service delivery, including in rural and remote areas. However, digital adoption among communities in these regions remains inconsistent and often hindered by infrastructural and socio-cultural constraints. This study aims to assess the digital readiness of rural communities in adopting mobile-based public service information systems, with a specific focus on understanding the social and technological dynamics that shape their engagement. Employing a mixed methods approach with an explanatory sequential design, the research began with a structured survey involving 150-200 respondents per location, followed by in-depth interviews with key informants such as village officials, service operators, and local users. The quantitative data were analyzed using SPSS to identify general patterns in digital readiness based on the Technology Readiness Index and the Digital Readiness Framework, while qualitative insights were thematically analyzed using NVivo to uncover contextual factors. The findings reveal that while some respondents exhibit a moderate level of digital optimism, barriers such as unstable internet access, limited digital literacy, and fear of misusing technology significantly affect adoption rates. Furthermore, social support from family members emerged as a critical facilitator in overcoming these challenges. This study contributes to the discourse on inclusive digital transformation by highlighting the importance of integrating community-based support mechanisms into system design and policy planning. The implications suggest that successful digitalization efforts in rural areas must go beyond infrastructure development and address the social readiness of users through culturally sensitive and participatory approaches.